PSYCOLOGICAL EFFECTS OF COMPUTER VISION SYNDROME AND IT’S AYURVEDIC MANAGEMENT - PATIL, DR. NEETA R.; PATIL, DR. KIRAN B.; DHOBE, DR. OJAS; SONUNUE, DR POOJA; THAKARE, DR. VRUSHALI R.; DALE, DR. BHAGYASHRI R. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
With the increasing digitalization of work, lifestyle and education, Computer Vision Syndrome (CVS) has become a prevalent health issue, characterised by the combination of both ocular and psychological symptoms. While local ocular symptoms such as dryness of eyes, eye strain and visual fatigue are recognised, the psychological effects such as irritability, mental fatigue, mood disturbances, anxiety, depression, and insomnia are often neglected and poorly addressed in conventional care. This narrative review aims to explore the psychosomatic dimensions of CVS, interpret its pathophysiology through Ayurvedic principles, and outline holistic management strategies that integrate traditional and modern approaches. This review of classical Ayurvedic texts, modern clinical studies and recent integrative health literature was conducted to recognize overlaps in causative factors, symptomatology, and treatment framework for CVS with psychological components. CVS shares notable similarities with Shushkakshipaka (dry eye syndrome), a Sarvagata Netra Roga(all eye diseases) described in Ayurveda. Disturbances in Manovaha Srotas (channels related to mind) and the vitiation of Alochaka Pitta, Prana Vata and Tarpaka Kapha account for the dual ocular and psychological symptoms. Netra Tarpana (nourishment to eye), Nasya (medicine administration through nose), Shirodhara (oil flow therapy), Medhya Rasayana (cognitive enhancer), Yoga(postures) and Pranayama (breath work) and lifestyle modifications provide targeted relief while improving overall mental health and visual resilience. Ayurveda offers a thorough and individualised approach for managing CVS and its psychological impacts. Integrating Ayurvedic principles with digital ergonomics and contemporary behavioural science can enhance the prevention, treatment and quality of life in individuals affected by this new digital-age disorder.